On Genocchi Numbers and Polynomials - Seog-Hoon Rim; Kyoung Ho Park; Eun Jung Moon (Abstract and Applied Analysis)
The main purpose of this paper is to study the distribution of Genocchi polynomials. Finally, we construct the Genocchi zeta function which interpolates Genocchi polynomials at negative integers.